Description of Parental Feeding Pattern in Toddler Child - Qonita Huwaida; Siti Arifah (Indonesian Journal of Global Health Research, 2024)
The age of toddler is a golden age because the growth and development of children at this age takes place quickly and both physically, cognitively, emotionally, and socially. A good feeding pattern is useful to meet the nutritional needs they need, a good diet will also play a role in preventing nutritional problems. This study aims to describe the feeding patterns of parents in toddler-age children in Polokarto Village, Polokarto District. This research is an analytical descriptive research. The research sample consisted of 136 mothers who had toddler-age children who were taken by purposive sampling. Data collection was carried out using a questionnaire of demographic data and feeding patterns. The analysis used in this study is a univariate analysis that will be displayed in the form of distribution, frequency, and percentage. The results of the study showed that the majority of parents had the quality of feeding patterns that were included in the sufficient category, namely 79 respondents (58.1%). Most of the respondents were in the age range of 27-33 years, namely 84 respondents (61.8%). Then the majority of parents have a high school education background and almost all mothers have the status of housewives (72.8%).